Impact Factors Influencing Budgetary Savings in Public Procurements in Ukraine - Nataliia TKACHENKO; Alexander Baranovsky; Oksana POLINKEVYCH; Natallia CHYZH; Kateryna Bogatyrova; Iryna Zelenitsa (Communications of International Proceedings, 2020)
One of the main functions of the state is the purchase of goods, works and services to meet public needs. More than 30 thousand tender organizers are undertaking procurement activities in Ukraine in the public sector of the economy. The annual volume of public procurements in 2018 amounts to more than 300 billion UAH (8.5% of Ukraine’s GDP).  The aim of the study is to identify the factors that affect real budgetary savings of public procurements. Using the method of economic and statistical analysis, the influence of intensity of competition and expected procurement value on the amount of budgetary savings has been investigated and the factors that reduce public procurements efficiency have been identified. The hypothesis of the study is that the value of budgetary savings in public procurements cannot be determined as the difference between the expected and the actual value of the purchase in the absence of a common methodology for determining the expected value of the purchase. It is proved that the lack of automatic price monitoring in the electronic system ProZorro, low level of competition in the tenders, significant losses due to the violation of the law by the customer and the improper performance of the economic and legal relations by the entities of the procurement contract are negative factors that influence the efficiency of public procurements. In the age of digital transformation, the determination of fair purchase value is determined automatically, which prevents the buyers from purchasing products at inflated prices and hereby report on achieving economy.
Keywords: Public Procurements; Public Tenders; Intensity of Competition; Budgetary Savings.